Associations between Bone Mineral Density and WOMAC Scores in Healthy Individuals: Insights from the Qatar Biobank - Mohammed Al-Hamdani (16962702) (2024)
Background Bone mineral density (BMD) is an indicator of bone health that predicts future bone fractures. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) is used to assess the severity of symptoms related to pain, stiffness, and function in diseased hip and knee joints. Here we assessed whether BMD measured at specific sites predicts WOMAC scores in healthy individuals whilst controlling for sociodemographic variables. Methodology BMD, sociodemographic, and WOMAC data were collected from 1764 healthy adult individuals attending the Qatar Biobank (QBB). Multiple linear regression was used to examine associations between sociodemographic factors, total body BMD and BMD related to specific skeletal sites (including femoral (femoral neck and trochanter), trunk, pelvis and total spine), and the three WOMAC subscales (pain, stiffness, and physical function). Results After controlling for sociodemographic variables, total body and specific BMD measures did not predict pain. However, BMD measures significantly contributed to predicting stiffness after controlling for sociodemographic variables (R2 = 0.065, ΔF(7, 1724) = 3.34, p= 0.002), with a higher total body BMD associated with increased stiffness and a higher trunk BMD associated with decreased stiffness. Total body BMD measures also significantly contributed to predicting compromised physical function (R2 = 0.091, ΔF(7, 1724) = 3.762, p < 0.001) after controlling for sociodemographic variables, with a higher total body BMD associated with an increase in compromised physical function. Conclusion Total body BMD seems to be a more important predictor of stiffness and physical function than specific skeletal sites BMD measures. Monitoring BMD may have important implications for osteoarthritis patients. Other Information Published in: Journal of Clinical Densitometry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jocd.2024.101547